Immuno biology - Kenneth Murphy (Garland Science, 2008)
Serves as an introductory text for use in immunology courses for undergraduates, graduate students and medical students. This book guides the reader through the immune system in different aspects - from the first engagement of innate immunity to the generation of the adaptive immune response and its clinical consequences.